Changes in sleep behavior, sleep problems, and psychological distress/health-related quality of life of young Japanese individuals before and during the COVID-19 pandemic. (3rd June 2022) - Tanioka, Kosuke; Kayaba, Momoko; Tomishima, Sayaka; Komada, Yoko; Inoue, Yuichi
ABSTRACT: Social restrictions during the coronavirus disease (COVID-19) pandemic have impacted sleep behavior and sleep problems, and their related daytime functioning in young adults. However, no studies have examined such changes in young individuals from countries with mild infection intensity and social restrictions. Therefore, we focused on sleep behaviors and sleep issues in young people in Japan. This study was conducted before and after the pandemic (October 2019 and May 2020, respectively). In total, 2, 222 (1, 371 students and 851 workers) individuals participated and completed anonymous Web-based questionnaires concerning demographic characteristics, sleep behaviors, sleep problems using the Japanese version of the Epworth Sleepiness Scale (JESS) and the Athens Insomnia Scale (AIS-J), psychological distress using the Japanese version of the Kessler Psychological Distress Scale, and health-related quality of life (HRQoL) evaluated with the Short Form-8 (SF-8). A significantly delayed sleep phase was observed in the second survey compared to the first (p < .001) and was more pronounced in students than in workers (p < .001). The total sleep time, social jetlag degree, and JESS, AIS-J, and SF-8 scores were significantly improved after the pandemic (p < .001, p < .001, p < .001, p < .001, p < .05, and p < .001, respectively). Careful monitoring of whether these modest changes can lead to adjustment concerns is needed.